Low affinity binding of plasma proteins to lipid-coated quantum dots as observed by in situ fluorescence correlation spectroscopy1. Issue 22 (14th June 2015) - Klapper, Yvonne; Maffre, Pauline; Shang, Li; Ekdahl, Kristina N.; Nilsson, Bo; Hettler, Simon; Dries, Manuel; Gerthsen, Dagmar; Nienhaus, G. Ulrich
<x xml:space="preserve">Abstract</x> Extremely low binding affinities of plasma proteins to MHPC lipid-enwrapped quantum dots have been revealed by fluorescence correlation spectroscopy measurements.